The frequency of hyperuricemia with left ventricular hypertrophy in patient with primary hypertension in Erbil city-Iraq - Naser Zangana, Salam; Hasan Alwan, Mohammed; A. Allaw, Salih (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: High serum uric acid level is common in hypertension and it may be correlatedwith left ventricular hypertrophy. The frequency of hyperuricemia is not previously wellinvestigated in Erbil city. Objectives: The objective of this study was to investigate thefrequency of hyperuricemia and the association between serum uric acid levels and leftventricular hypertrophy in a group of hypertensive patients in Erbil-Iraq. Patients and methods:A cross-sectional study was conducted in Rizgary teaching hospital between September 2015and September 2016. A total of 150 consecutive adult patients presenting with primaryhypertension were included. Based on the results of the echocardiography, the patients wereclassified into two groups; Group I (patients with left ventricular hypertrophy) and Group II(patients with non- left ventricular hypertrophy). The effects of high serum uric acid level on leftventricular mass and geometry were evaluated in both groups. Results: High serum uric acidlevel was present in 38 patients (25.3%). Based on the results of echocardiographic examination,left ventricular hypertrophy was present in 78 patients (52%), 25 of them (32 %) hadhyperuricemia. The mean of serum uric acid level, means of age, systolic blood pressure,diastolic blood pressure and lipid profile significantly higher in group I patients compared tothose in group II patients. Regarding echocardiographic parameters, There were significantlyhigher in hyperuricemic patients compared to patients without hyperuricemia the means ofinterventricular septal thickness, left atrium and left ventricular mass. Conclusions: In this study,high serum uric acid level was common in hypertensive patients and it was positively associatedwith left ventricular hypertrophy and dyslipidemia.